PERANCANGAN BUKU ILUSTRASI LAGU DOLANAN BOCAH DWI BAHASA JAWA-INDONESIA - Iffah Izzatun Nida S1 (Saraswati)
ABSTRACTThe decline in the creation of children’s song in the last few years it feels so apprehensive due to the negative impact on children. Impressions on television increasingly support the tunes are lively reply romance for consumption of children.Children are more focused on lucrative television show less beneficial for a child, because television shows prefer viewing events which have a high rating. While the event weakned children with teen romance events. Not only with event movies, children’s songs ever seeming to disappear are covered with love songs. Even children emerged with the duplication of the adult song. With anunprecedented spectacle deserved to children, psychological child forced to live mature more quickly, to be seen from talk, behavior style to the thinking of child. Its different from 10 years ago where kids play more often and gathered outside the house by singing and playing children’s games, espessially on the island of Java,various dolanan bocah songs imaginable on Java island invites kids to socialize as well as divert from the monitor’s hypnotic to the nature’s playground.Keyword : Monitor’s Hypnotic, Dolanan Bocah songs, illustration book songs